2011
DOI: 10.1128/aem.00104-11
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Screening of Pichia pastoris Strains with Enhanced Protein Production by Use of Microengraving

Abstract: The selection of highly productive cell lines remains a key step for manufacturing therapeutic proteins. Microengraving was used to screen chemically mutagenized populations of Pichia pastoris for increased production of an Fc fragment. Clones retrieved following three rounds of mutagenesis yielded titers 2.65-fold greater than those of the parental strain.Therapeutic proteins account for more than $99 billion of drug revenues annually worldwide (14) and account for a quarter of all new drugs for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…A compromise between the uniformity and speed of analysis by FACS and traditional cultivation (with its loss of information at the single cell level) is provided by the technique of micro-engraving, an emerging method for highthroughput analysis of secreted products from single cells (Love et al, 2006). Microengraving is a soft lithographic method based on intaglio printing to generate microarrays comprising secreted products from single cells, and has been used for screening a variety of secreted recombinant proteins (Panagiotou et al, 2011) as well as to characterise the secretome of B cells (Story et al, 2008). Interestingly, this method provides useful insights into secretion dynamics, showing, for example, how such a process is not linked to the cell cycle, but varies stochastically within a single cell during cell duplication.…”
Section: Single Cell Level Perspective On Productionmentioning
confidence: 99%
“…A compromise between the uniformity and speed of analysis by FACS and traditional cultivation (with its loss of information at the single cell level) is provided by the technique of micro-engraving, an emerging method for highthroughput analysis of secreted products from single cells (Love et al, 2006). Microengraving is a soft lithographic method based on intaglio printing to generate microarrays comprising secreted products from single cells, and has been used for screening a variety of secreted recombinant proteins (Panagiotou et al, 2011) as well as to characterise the secretome of B cells (Story et al, 2008). Interestingly, this method provides useful insights into secretion dynamics, showing, for example, how such a process is not linked to the cell cycle, but varies stochastically within a single cell during cell duplication.…”
Section: Single Cell Level Perspective On Productionmentioning
confidence: 99%
“…The methylotrophic yeast secrete protein more effectively than S. cerevisiae because they have a stacked Golgi apparatus adjacent to the ER, better organized to facilitate secretion (Preuss, Mulholland, Franzusoff, Segev, & Botsteint, ). Biological studies and strain engineering, however, have shown that there is potential to improve other bottlenecks in secretion by P. pastoris (Idiris, Tohda, Kumagai, & Takegawa, ; Panagiotou et al, ). In contrast, filamentous fungi are very effective secretors.…”
Section: Purification Processmentioning
confidence: 99%
“…As the final step in optimizing the SPB workflow, we iterated process variables that could affect cell viability during processing and recovery from hydrogel blocks. Viable cell isolation is crucial for the recovery of usable biological materials for downstream assays and single‐cell or clonal growth, which are of broad interest for many biological applications, such as selecting yeast and bacteria for bioproduction, and the analysis of various clonal populations in biology, such as B and T cells in immunology or circulating tumor cells in oncology . Notably, MWAs have been used to screen and clone cells, but the upper limit has remained approximately 100 cells per array by a manual recovery method .…”
Section: Resultsmentioning
confidence: 99%